Reliable identification of women with CIN3+ using hrHPV genotyping and methylation markers in a cytology‐screened referral population. Issue 1 (18th November 2018) - Leeman, Annemiek; del Pino, Marta; Marimon, Lorena; Torné, Aureli; Ordi, Jaume; ter Harmsel, Bram; Meijer, Chris J.L.M.; Jenkins, David; Van Kemenade, Folkert J.; Quint, Wim G.V.
Abstract : Cervical screening aims to identify women with high‐grade squamous intraepithelial lesion/cervical intraepithelial neoplasia 2‐3 (HSIL/CIN2‐3) or invasive cervical cancer (ICC). Identification of women with severe premalignant lesions or ICC (CIN3+) could ensure their rapid treatment and prevent overtreatment. We investigated high‐risk human papillomavirus (hrHPV) detection with genotyping and methylation of FAM19A4/miR124‐2 for detection of CIN3+ in 538 women attending colposcopy for abnormal cytology. All women had an additional cytology with hrHPV testing (GP5+/6+‐PCR‐EIA+), genotyping (HPV16/18, HPV16/18/31/45), and methylation analysis (FAM19A4/miR124‐2) and at least one biopsy. CIN3+ detection was studied overall and in women <30 ( n = 171) and ≥30 years ( n = 367). Positivity for both rather than just one methylation markers increased in CIN3, and all ICC was positive for both. Overall sensitivity and specificity for CIN3+ were, respectively, 90.3% (95%CI 81.3–95.2) and 31.8% (95%CI 27.7–36.1) for hrHPV, 77.8% (95%CI 66.9–85.8) and 69.3% (95%CI 65.0–73.3) for methylation biomarkers and 93.1% (95%CI 84.8–97.0) and 49.4% (95%CI 44.8–53.9) for combined HPV16/18 and/or methylation positivity. For CIN3, hrHPV was found in 90.9% (95%CI 81.6–95.8), methylation positivity in 75.8% (95%CI 64.2–84.5) and HPV16/18 and/or methylation positivity in 92.4% (95%CI 83.5–96.7). In women aged ≥30, the sensitivity of combined HPV16/18 and methylation was increased (98.2%, 95%CI 90.6–99.7) with a specificity of 46.3% (95%CI 40.8–51.9). Combination of HPV16/18 and methylation analysis was very sensitive and offered improved specificity for CIN3+, opening the possibility of rapid treatment for these women and follow‐up for women with potentially regressive, less advanced, HSIL/CIN2 lesions. Abstract : What's new? Reliable triage of women with cervical intraepithelial neoplasia (CIN) is of high priority as not all lesions progress to invasive carcinoma. Here the authors show that combining the methylation status of tumor suppressor genes FAM19A4 and miR124‐2 with genotyping for high‐risk human papillomavirus results in a highly sensitive and moderately specific triage strategy that identifies women with CIN lesions likely to need rapid treatment. The authors recommend clinical evaluation of the strategy in prospective studies.